The Concept of Humanitarian Intervention and Applicable International Law - J. K. Shaiymbetova (Московский журнал международного права, 2009)
The concept of humanitarian intervention is one of the main problems of contemporary world order. The point is that the humanitarian intervention is legally inconsistent. The term “humanitarian intervention” was brought into service by western states and scientists to justify the use of military force against other state for human rights protection in this state, against will of its government.Humanitarian intervention may be defined as the use of force by one or more states against another state with the aim of protection of human rights – citizens of this state that is human rights protection within the territory of another state without either the permission of its legitimate government or the authorization of the UN Security Council.The article considers the content of humanitarian intervention, as well as its differentiation from the closely-related concepts. It is necessary because of the term “humanitarian intervention” is doctrinal construction; there is no acknowledged international instrument which gives a definition of this term.The conclusion of the article is to show the illegality of humanitarian intervention. The task is that international cooperation for the human rights protection in crisis situations develops within contemporary applicable international law.